The impact of business support services on the payment of social grants in the Free State province - Setsabi S. Matsoso; Moses M. Gasela (Africa’s Public Service Delivery & Performance Review, 2024)
Background: South African Social Security Agency (SASSA) plays a significant role in alleviating socio-economic challenges in the Free State province of South Africa. Yet, little is known as to whether business support services influence the payment of social grants in the Free State province. This study was hence intended to fill this gap.